A label-free electrochemical test for DNA-binding activities of tumor suppressor protein p53 using immunoprecipitation at magnetic beads - Nemcová, Katerina; Havran, Ludek; Sebest, Peter; Brázdová, Marie; Pivonková, Hana; Fojta, Miroslav (Analytica chimica acta, 2010)
In this paper we extend the application area of the label-free structure-sensitive electrochemical DNA sensing with mercury-based electrodes which is for the first time used, in combination with immunoprecipitation at magnetic beads (MB), for the probing of DNA interactions with tumor suppressor protein p53. The technique relies on capture of the p53-DNA complexes at MB via anti-p53 antibodies, followed by salt-induced dissociation of linear DNA from the complex and its voltammetric detection. Competitive binding of p53 to various plasmid DNA substrates, including lin or scDNAs with or without a specific target site, can easily be followed by ex situ electrochemical analysis of DNA recovered from the immunoprecipitated complexes. Compared to gel electrophoresis which is usually applied to analyze different plasmid DNA forms and their complexes with proteins, the electrochemical detection is faster and allows simpler quantitation of DNA containing free ends at submicrogram levels. We demonstrate applicability of the proposed technique to monitor different DNA-binding activities of wild type and mutant p53 proteins.
Keywords: Binding, Competitive; Electrodes; vazebná místa; rtuť; biosenzitivní techniky; Mercury; Electrophoresis, Agar Gel; nádorový supresorový protein p53; Electrochemical Techniques; Immunoprecipitation; kompetitivní vazba; elektrody; elektrochemické techniky; Biosensing Techniques; Binding Sites; Animals; lidé; magnetismus; Magnetics; Humans; zvířata; imunoprecipitace; myši; DNA; Mice; elektroforéza v agarovém gelu; Tumor Suppressor Protein p53